Development of a new Sandvik ‘little brother’ dynamic rockbolt and the in situ dynamic evaluation of bolts - Roach, W; Rataj, M; Darlington, B (Ground Support 2019: Ninth International Symposium on Ground Support in Mining and Underground Construction, 2019)
Since the Australian mining industry’s embracement of the D47 Mechanical Dynamic Extra (MDX) bolt, Sandvik has recently developed a smaller diameter version, the D39 MDX bolt. Sized for the Canadian, North American and European markets, the D39 MDX is similarly suitable for broken, very weak, strong and seismic rock conditions. The major challenge during the design phase was determining how to fit the components into the smaller envelope while maintaining the desired dynamic capacity. To test the performance of the D39 MDX bolt, the unique and well-proven Sandvik Dynamic Test Rig (DTR) was used. The DTR is a portable apparatus that simulates a seismic event by applying a dynamic impulse of up to 35 kJ. The DTR records the load and displacement of the test bolt through a series of sensors. The test bolts can be installed in any mine site using standard installation procedures and bolting machinery. Tests performed at mines showed the bolt is typically capable of absorbing an energy of 25 kJ (single impact) with displacements in the range of 120–143 mm. The tests conducted have proven that the DTR can be used efficiently in bolt development, and it opens a considerable window of opportunity for future development and evaluation of dynamic rockbolts in actual conditions as opposed to in the laboratory environment. The DTR also provides an opportunity to study the effects of mining progression on bolt performance as test bolts can be tested at any time interval after installation.
Keywords: rockbolt; dynamic; dynamic testing; seismic; in situ; ground support